2018
DOI: 10.7150/jca.22119
|View full text |Cite
|
Sign up to set email alerts
|

mTOR signaling-related MicroRNAs and Cancer involvement

Abstract: MicroRNAs (miRNAs) are a class of single-stranded RNAs, 18-23 nucleotides in length that regulate gene expression at the post-transcriptional level. Dysregulation of miRNAs has been closely associated with the development of cancer. In the process of tumorigenesis, mammalian target of rapamycin (mTOR) plays important roles, and the mTOR signaling pathway is aberrant in various types of human cancers, including non-small cell lung cancer (NSCLC), breast cancer, prostate cancer, as well as others. However, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 117 publications
2
24
0
Order By: Relevance
“…Currently, the mTORC1 inhibitors, rapamycin as well as its analogues have been approved for the treatment of several types of human cancer, such as renal cell carcinoma, mantle cell lymphoma, and some TSCrelated tumors, including lymphangioleiomyomatosis, angiomyolipomas, and subependymal giant cell astrocytomas [6,[16][17][18]. Numerous studies indicate that mTORC1 signaling pathway is regulated by miRNAs [10]. However, little is known about how miRNAs function in the dysregulated mTORC1mediated tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the mTORC1 inhibitors, rapamycin as well as its analogues have been approved for the treatment of several types of human cancer, such as renal cell carcinoma, mantle cell lymphoma, and some TSCrelated tumors, including lymphangioleiomyomatosis, angiomyolipomas, and subependymal giant cell astrocytomas [6,[16][17][18]. Numerous studies indicate that mTORC1 signaling pathway is regulated by miRNAs [10]. However, little is known about how miRNAs function in the dysregulated mTORC1mediated tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to carcinogenesis, miRNAs can act as either oncogenes or tumor suppressors, depending on the genes they regulate and the cellular context [9]. Numerous studies have shown that dysregulation of miRNAs plays an essential role in tumorigenesis through modulation of AKT/mTORC1 signaling pathway [10]. However, the function of miRNAs in mTORC1-induced tumorigenesis remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The mTOR pathway plays as a critical effector in cell signaling pathways that regulates various cellular processes including apoptosis, autophagy, protein synthesis, and energy metabolism . It has been recently demonstrated that there are several miRNAs that oppose mTOR signaling and might have potential therapeutic implications in cancer therapy (summarized in Figure ) …”
Section: Mirnas Are Involved In Mtor Suppression In Cancersmentioning
confidence: 99%
“…Due to its antiproliferative properties, mTOR inhibitors have also been approved as anticancer drugs [ 280 282 ]. Intriguingly, the identification of miRNAs as novel emerging regulators of mTOR signaling has provided new insights into a multitude of biological processes, especially in tissue remodeling and hypertrophy, which has been appreciated by the scientific community in cardiac physiology [ 103 , 169 , 185 ]. Hypertrophic stimuli such as phenylephrine [ 283 ], angiotensin II (Ang II) [ 37 , 284 , 285 ], and endothelin-1 [ 286 ] are known to activate mTORC1 in the heart and result in robust vascular remodeling leading to heart failure [ 274 ].…”
Section: Mtor In Cardiovascular Diseasesmentioning
confidence: 99%